2022
DOI: 10.3390/ijerph19073932
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for In-Hospital Death Due to COVID-19 in Patients Hospitalised at the Temporary Hospital Located at the National Stadium in Warsaw: A Retrospective Analysis

Abstract: The outbreak of the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) pandemic has affected all aspects of social life and brought massive changes to the healthcare sector. The aim of this study was to identify the factors affecting the mortality of COVID-19 patients at a temporary hospital in Warsaw (Poland). The present study was conducted based on a retrospective analysis of the medical records of patients hospitalised at the temporary hospital located at the National Stadium in Warsaw between 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…The present study reports comprehensive characteristics of patients with SARS-CoV-2 infection admitted to the ED of the Central Clinical Hospital of the Ministry of Interior and Administration in Warsaw. In addition, it complements our previous study concerning COVID-19 patients hospitalized at the temporary hospital in Warsaw [ 69 ]. The findings from the present study can be used for international comparisons aimed at developing the best strategies for the management of patients with COVID-19.…”
Section: Discussionsupporting
confidence: 71%
“…The present study reports comprehensive characteristics of patients with SARS-CoV-2 infection admitted to the ED of the Central Clinical Hospital of the Ministry of Interior and Administration in Warsaw. In addition, it complements our previous study concerning COVID-19 patients hospitalized at the temporary hospital in Warsaw [ 69 ]. The findings from the present study can be used for international comparisons aimed at developing the best strategies for the management of patients with COVID-19.…”
Section: Discussionsupporting
confidence: 71%
“… 7 , 8 This approach eliminates confirmed asymptomatic carriers or patients with mild cases of COVID-19 as a source of transmission. 8 , 13 , 16 Experiments from some regions have shown that Fangcang shelter hospitals are feasible and do not require a large amount of investment, although further improvements and complete systems are needed in terms of form, regulation, and treatment procedures. 14 , 15 , 17 , 18 The management mode of Shanghai Fangcang shelter hospital has been further optimized and upgraded in the following aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil [ 18 ], the Riocentro Campaign Hospital in Rio of Janeiro had a mortality of 25.5% (194/761 patients) and was associated with age and pulmonary impairment. In Poland [ 16 ], the National Stadium in Warsaw had a mortality of 8.91% (156/1749 patients), identifying 14 factors (some comorbidities, stroke history, chronic obstructive pulmonary disease, and heart failure) that have a significant impact on the prognosis and mortality. In South Africa [ 17 ], the International Convention Centre in Cape Town had a mortality of 5.7% (83/1502 patients), highlighting that the daily communication with the whole care service platform was a critical success factor.…”
Section: Discussionmentioning
confidence: 99%
“…In February 2020, China put the first three temporary hospitals (Fangcang, Huoshenshan, and Leishenshan) into operation in response to insufficient medical resources, limiting the national spread and reducing the number of deaths [ 10–13 ]. In the following weeks, various countries implemented similar measures, mainly in cities with the highest number of cases such as Madrid and Asturias in Spain [ 14 , 15 ], Warsaw in Poland [ 16 ], Cape Town in South Africa [ 17 ], Sao Paulo in Brazil [ 18 ] and New York in the United States of America [ 19 ].…”
Section: Introductionmentioning
confidence: 99%